Triumph against cancer: invading colorectal cancer with nanotechnology. (2nd September 2021) - Vinchhi, Preksha; Patel, Mayur M.
ABSTRACT: Introduction: Recent statistics have reported colorectal cancer (CRC) as the second leading cause of cancer-associated deaths in the world. Early diagnosis of CRC may help to reduce the mortality and associated complications. However, the conventional diagnostic techniques often lead to misdiagnosis, fail to differentiate benign from malignant tissue or diagnose only at an advanced stage. For the treatment of CRC, surgery, chemotherapy, immunotherapy, and radiotherapy have been employed. However, the quality of living of the CRC patients is highly compromised after employing current therapeutic approaches owing to the toxicity issues and relapse. Area covered: This review accentuates the molecular mechanisms involved in the pathogenesis, stages of CRC, conventional approaches for diagnosis and therapy of CRC and the issues confronted thereby. It provides an outlook on the advantages of employing nanotechnology-based approaches for prevention, early diagnosis, and treatment of CRC. Expert opinion: Employing nanotechnology-based approaches has demonstrated promising outcomes in the prevention, diagnosis, and treatment of CRC. Nanotechnology-based approaches can surmount the major drawbacks of traditional diagnostic and therapeutic approaches. Nanotechnology bestows the advantage of early detection of CRC which helps to undertake instant steps for offering efficient therapy and reducing the mortality rates. For the treatment of CRC, nanocarriers offer the benefit of achieving controlled drug release, improved drug bioavailability, enhanced tumor targetability and reduced adverse effects.